Crafting Instructions Collaboratively: Student Questions and Dual Addressivity in Classroom Task Instructions. Issue 4 (18th May 2016) - St. John, Oliver; Cromdal, Jakob
Abstract : This study examines classroom task instructions—phases traditionally associated with noninteractional objectives and operations—and reveals their composition as interactionally complex and cocrafted. Analyses of video sequences of task instructional activity from three different secondary school lessons show that student questions routinely contribute to making task instructions followable . In this environment, student questions set up tensions between the demand to respond to the individual and responsibility to uphold the general instructional agenda. Data show that, as addressees of student questions, instructors take great care to meet both individual and collective accountabilities. To meet obligation to the addressee and exploit the instructional benefit of the question for the cohort, dual addressivity —targeting two or more addressees in response to a student question—proves a crucial method for achieving such principled practice. Educationally, it appears vital to recognize student instructed action as integral to task-related learning.